The Technic and Cost of Jabon (Anthocephalus cadamba Miq.) Cultivation by The Farmer of Community Forest - Nurheni Wijayanto; Adisti Permatasari Putri Hartoyo (Jurnal Silvikultur Tropika, 2013)
Jabon (A. cadamba) has been cultivated in Bogor community forest since 2008. Research about technic and cost of jabon cultivation in the community forest is needed because difference by location and probably has impact to difference in output, such as in the wood volume. Identification technic and cost of jabon cultivation has been done toward 11farmers of Bogor community forest by purposive sampling. Assumption in this research are similarity in site and not occurring economy fluctuation. The result showed that, pattern cropping that generally applied is agroforestry. The components of jabon cultivation technic that more complete applied by the respondent A1, C2, C3, and B4 rather than others respondent in the every age class. More complete cultivation components in the practice allegedly produce higher volume. The highest cost of jabon cultivation expended by respondent B1, B2, C3, and B4 in the every age class. The total cost of jabon cultivation didn’t influences jabon volume.Keywords: cultivation cost, cultivation technic, jabon, the farmers of the society forest